2015
DOI: 10.1016/j.jceh.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Riddle of Nonalcoholic Fatty Liver Disease: Progression From Nonalcoholic Fatty Liver to Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic fatty liver (NAFL) is an emerging global epidemic which progresses to nonalcoholic steatohepatitis (NASH) and cirrhosis in a subset of subjects. Various reviews have focused on the etiology, epidemiology, pathogenesis and treatment of NAFLD. This review highlights specifically the triggers implicated in disease progression from NAFL to NASH. The integrating role of genes, dietary factors, innate immunity, cytokines and gut microbiome have been discussed. ( J CLIN EXP HEPATOL 2015;5:147-158)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 153 publications
(132 reference statements)
3
96
0
14
Order By: Relevance
“…It has been suggested that insulin resistance plays a pathogenic role in kidney disease progression by worsening renal hemodynamics by activation of the sympathetic nervous system, sodium retention and down-regulation of the natriuretic peptide system 42 , making insulin resistance a possible mechanistic link between NAFLD and CKD. NF-kB pathway activation in NASH increases the transcription of a variety of proinflammatory genes that can amplify systemic chronic inflammation 43,44 . Hence, the increased intra-hepatic cytokine production that occurs in NAFLD/NASH is likely to play a pathogenic role also in the development of extra-hepatic complications, such as CVD and CKD.…”
Section: Predisposing Factors Contributing To Nash: Diet Insulin Resmentioning
confidence: 99%
“…It has been suggested that insulin resistance plays a pathogenic role in kidney disease progression by worsening renal hemodynamics by activation of the sympathetic nervous system, sodium retention and down-regulation of the natriuretic peptide system 42 , making insulin resistance a possible mechanistic link between NAFLD and CKD. NF-kB pathway activation in NASH increases the transcription of a variety of proinflammatory genes that can amplify systemic chronic inflammation 43,44 . Hence, the increased intra-hepatic cytokine production that occurs in NAFLD/NASH is likely to play a pathogenic role also in the development of extra-hepatic complications, such as CVD and CKD.…”
Section: Predisposing Factors Contributing To Nash: Diet Insulin Resmentioning
confidence: 99%
“…NAFLD is the most common liver disorder and is the leading cause of hepatocyte injury and fibrosis. NAFLD is also associated with chronic liver diseases such as cirrhosis [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The first hit initiates LS, and the second hit stimulates inflammatory processes. These two conditions may result in hepatocyte injury and fibrosis [4,5]. NAFLD is asymptomatic, undetectable, and progressive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations